Stratified Bacterial and Archaeal Community in Mangrove and Intertidal Wetland Mudflats Revealed by High Throughput 16S rRNA Gene Sequencing - Zhou, Zhichao; Meng, Han; Liu, Yang; Gu, Ji-Dong; Li, Meng (Frontiers in Microbiology, 2017)
The stratified distribution of bacterial and archaeal communities has been detected in many sediment profiles from various natural environments. A better understanding of microbial composition and diversity pattern in coastal mangrove wetlands in relation to physicochemical and spatial-temporal influences could provide more insights into the ecological functions of microbes in coastal wetlands. In this study, seasonal variations of microbial communities within sediment profiles from two sediment types (mangrove forest and intertidal mudflats) at three sampling locations in coastal Mai Po wetland were characterized using MiSeq high throughput sequencing and 16S rRNA quantitative PCR methods. Bacterial 16S rRNA gene abundance showed clear decreasing trends with increasing depth for all site, seasonality and sediment types. There is a weak seasonal dynamic of bacterial and archaeal community abundance in both seasons. Seasonality imposed more influence on the beta diversity pattern of bacterial community than archaeal community. The five most abundant phyla within bacterial and archaeal community remain stable between two distinctive seasons. Sediment depth and seasonality are the most influential factors affecting bacterial community composition and diversity. The pH is the most influential factor on shaping the archaeal community. Stratified distribution of bacterial community including aerobic and anaerobic bacterial taxa is largely represented in the surface layer and the subsurface layers, respectively. For archaeal stratification, Thaumarchaeota Marine Group I is the dominant member in surface sediments while Bathyarchaeota and MBG-B (Lokiarchaeota) dominate in subsurface sediments. Such stratified distribution patterns are irrespective of sediment types, sampling locations or seasonality, but significantly correlated to the sediment depth, which might be shaped by oxygen availability and the distribution of other terminal electron accepters along the depth profile.